2013
DOI: 10.1371/journal.pone.0076724
|View full text |Cite
|
Sign up to set email alerts
|

Ultradeep 16S rRNA Sequencing Analysis of Geographically Similar but Diverse Unexplored Marine Samples Reveal Varied Bacterial Community Composition

Abstract: BackgroundBacterial community composition in the marine environment differs from one geographical location to another. Reports that delineate the bacterial diversity of different marine samples from geographically similar location are limited. The present study aims to understand whether the bacterial community compositions from different marine samples harbour similar bacterial diversity since these are geographically related to each other.Methods and Principal FindingsIn the present study, 16S rRNA deep sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 36 publications
4
36
0
Order By: Relevance
“…and seagrass (Cymodocea sp. ), Karankadu coastal region, Indian (Aravindraja et al 2013). Proteobacteria can be observed in large amount in marine samples, which supported the phyla are ubiquity in the marine area, especially in the meadow habitats.…”
Section: Diversity Of Associated Bacterial Communitymentioning
confidence: 66%
See 2 more Smart Citations
“…and seagrass (Cymodocea sp. ), Karankadu coastal region, Indian (Aravindraja et al 2013). Proteobacteria can be observed in large amount in marine samples, which supported the phyla are ubiquity in the marine area, especially in the meadow habitats.…”
Section: Diversity Of Associated Bacterial Communitymentioning
confidence: 66%
“…The bacteria inside of seagrass are nearly ten times more than the unvegetated areas (Delille et al 1996). The distribution of microbial communities is highly environmental correlation and ecological limitation (Crump and Koch 2008;Newby et al 2006), owing to abiotic (nutrients, dissolved organic carbon and physical parameters) and biotic (constraints in community ecology) factors (Sundqvist et al 2013), especially, the coastal and estuarine areas, where they are characterized by sharp physical and chemical gradients (Aravindraja et al 2013;Ning et al 2004). Diverse bacterias associated with Halodule, Thalassodendron, Thalassia and Cymodocea and various prokaryotic epiphytes associated with the seagrass have been found in the Western Indian Ocean (WIO) and the east Africa (Hamisi et al 2007;Uku 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteria in the order Actinomycetales constitute a minor component of sediment communities (5,7,(31)(32)(33)(34)(35)(36), yet decades of culturing efforts have shown that they persist in most well-sampled sediments (37)(38)(39)(40). These bacteria are well known for secondary metabolite production (41), and their mycelial growth form creates the potential for the formation of large networks (42) that have yet to be spatially characterized.…”
mentioning
confidence: 99%
“…Several recent works (Aravindraja et al 2013;Bartram et al 2014;Bowen et al 2012;Dohrmann et al 2013;Gibbons et al 2013;Kim et al 2013;Logares et al 2013;Oh et al 2013;Portillo et al 2013;Sánchez et al 2013;Székely and Langenheder 2014;Wegner et al 2013), mainly performed with nextgeneration sequencing technologies, have demonstrated that most bacterial communities are composed of a few abundant taxa and a plethora of rare ones (Pedrós-Alió 2012). Such different fractions may have in theory different taxonomic signatures (at the various taxonomic levels), in relation to the physiological features of the groups of taxa present.…”
mentioning
confidence: 99%